2017
DOI: 10.1044/2017_ajslp-16-0098
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Communication-Related Quality of Life of Individuals With Oromandibular Dystonia Receiving Botulinum Toxin Injections

Abstract: CR-QoL was rated lower by participants with OMD as compared with control participants across all ASHA QCL domains/subdomains with "socialization/activities" and "confidence/self-concept" having the largest effect sizes. No differences in CR-QoL were found over the course of the treatment cycle. We advocate for outcome measures that include patient report. The use of patient-reported outcome measures in conjunction with objective or impairment-based outcome measures can help inform meaningful clinical indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…For example, individuals with OMD reported reductions in QoL related to socialization and activities, confidence and selfconcept, roles and responsibilities, and overall QoL. 34 These results demonstrate that OMD can have a pervasive impact across all aspects of QoL as it relates to communication.…”
Section: Management Of Psychosocial Issuesmentioning
confidence: 82%
See 3 more Smart Citations
“…For example, individuals with OMD reported reductions in QoL related to socialization and activities, confidence and selfconcept, roles and responsibilities, and overall QoL. 34 These results demonstrate that OMD can have a pervasive impact across all aspects of QoL as it relates to communication.…”
Section: Management Of Psychosocial Issuesmentioning
confidence: 82%
“…Dykstra (Page) and her colleagues have explored communicative participation in individuals with OMD using patient-reported questionnaires. 20,33,34 Across all studies, individuals with OMD have reported significant reductions in participation as compared with healthy control participants. The Voice Activity and Participation Profile (VAPP) was administered to an individual with focal lingual dystonia in a 2007 case study by Dykstra and colleagues.…”
Section: Management Of Psychosocial Issuesmentioning
confidence: 96%
See 2 more Smart Citations
“…In this study with 20 total patients (grouped as 10 control participants and 10 patients with oromandibular dystonia), dysarthria was assessed before and after treatment with the toxin. Significant differences were observed between the participating groups [25].…”
Section: Orofacial Dystoniamentioning
confidence: 92%